2013
DOI: 10.2337/dc13-0347
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Autonomic Neuropathy Affects Symptom Generation and Brain-Gut Axis

Abstract: OBJECTIVELong-term diabetes leads to severe peripheral, autonomous, and central neuropathy in combination with clinical gastrointestinal symptoms. The brain-gut axis thus expresses a neurophysiological profile, and heart rate variability (HRV) can be correlated with clinical gastrointestinal symptoms.RESEARCH DESIGN AND METHODSFifteen healthy volunteers and 15 diabetic patients (12 with type 1 diabetes) with severe gastrointestinal symptoms and clinical suspicion of autonomic neuropathy were included. Psychoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 35 publications
3
44
0
2
Order By: Relevance
“…More than 75% of diabetic patients show one or more GI symptoms such as early satiety, postprandial fullness, bloating, nausea, vomiting, constipation, diarrhea, abdominal pain, and fecal incontinence 35. It was reported that STZ injection led to gastric and colonic hypersensitivity,25,36 in addition to peripheral sensorimotor neuropathy in rats 24,37.…”
Section: Discussionmentioning
confidence: 99%
“…More than 75% of diabetic patients show one or more GI symptoms such as early satiety, postprandial fullness, bloating, nausea, vomiting, constipation, diarrhea, abdominal pain, and fecal incontinence 35. It was reported that STZ injection led to gastric and colonic hypersensitivity,25,36 in addition to peripheral sensorimotor neuropathy in rats 24,37.…”
Section: Discussionmentioning
confidence: 99%
“…As frequencies continue to rise, so do the populations of individuals with chronic states of disease (Amos et al 1997). Those with persistent T2D experience a host of secondary complications, including autonomic neuropathy, which affects many organs in the body (Wang et al 2008; Brock et al 2013). Injuries to the enteric nervous system (ENS) manifest through symptoms of gastropathy (dyspepsia, gastroparesis) and gastrointestinal (GI) dysmotility, and these commonly plague T2D patients (Camilleri and Malagelada 1984; Byrtzer et al 2001; Bagyánszki and Bódi 2012; Yarandi and Srinivasan 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The CPM efficacy is likely related to the generalized status of the central nervous system, and hence diabetes induced central impairment may likely interfere with this complex network [13][14][15]. Changes in pain modulation processes, as reflected by dynamic psychophysical tests, are now increasingly recognized as clinically relevant.…”
Section: Introductionmentioning
confidence: 99%